Secured Transactions, Collateral Registries and Movable Asset-Based Financing : Knowledge Guide - World Bank (World Bank, Washington, DC, 2019)
The main objective of this Knowledge Guide is to provide guidance to the World Bank Group (WBG) staff, donor institutions, government officials and other practitioners on the objectives and implementation of secured transactions reforms, as well as the factors that affect the implementation. Chapter one contains a discussion of the economic rationale for modern secured transactions systems, providing a background on the utility of the reforms and their roles within the broader credit infrastructure, as well as a detailed section on various secured lending products. Chapter two charts some recent trends that impact secured transactions that may have more profound effects in the regulatory space, especially prudential regulation of financial institutions with respect to the deployment of various credit products, or initiatives that have the potential to disrupt existing processes, such as distributed ledger and blockchain technologies. Chapter three provides lessons from the implementation of the reforms, highlighting the key elements of international best practices and the challenges to their implementation on the ground. The chapter goes beyond secured transactions laws and examines their impact on other legislation, highlighting the need for proper integration within the broader legal frame¬work. Chapter four addresses a number of aspects of the core building block of modern secured transactions regimes, an electronic registry for notices of security rights (collateral registry). This Chapter focuses on various design considerations and their implementation. Finally, chapter five outlines the key elements of public awareness and capacity building that are essential to the successful deployment of a reform that is designed to increase access to credit.